2016
DOI: 10.3390/w8100441
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Alternative Climate Data Sources for Hydrological Simulations in the Upstream of the Amu Darya River

Abstract: Abstract:The main objective of this study is to investigate alternative climate data sources for long-term hydrological modeling. To accomplish this goal, one weather station data set (WSD) and three grid-based data sets including three types of precipitation data and two types of temperature data were selected according to their spatial and temporal details. An accuracy assessment of the grid-based data sets was performed using WSD. Then, the performances of corrected data combination and non-corrected grid-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 67 publications
3
18
0
Order By: Relevance
“…The overall results of the analyses of the GCP data clearly revealed that the APHRODITE precipitation data resulted in the best performance of the three GCP data sources, based on the SWAT simulation graphical and statistical results. These results agree with the findings reported in several other studies, which showed that SWAT simulations executed with APHRODITE precipitation data performed very well in central Vietnam [23,24,80]; glacier influenced basins in mountainous regions in northwest China [81,82] and central Asia [83,84]; and a major tributary of the Yangtze River in central China [85]. Lauri et al [31] also found that executing the VMod hydrological model [86] with combined APHRODITE precipitation and NCEP-CFSR temperature inputs accurately replicated hydrological simulations based on surface climate inputs of the 795,000 km 2 Mekong River Basin in southeast Asia.…”
Section: Discussionsupporting
confidence: 93%
“…The overall results of the analyses of the GCP data clearly revealed that the APHRODITE precipitation data resulted in the best performance of the three GCP data sources, based on the SWAT simulation graphical and statistical results. These results agree with the findings reported in several other studies, which showed that SWAT simulations executed with APHRODITE precipitation data performed very well in central Vietnam [23,24,80]; glacier influenced basins in mountainous regions in northwest China [81,82] and central Asia [83,84]; and a major tributary of the Yangtze River in central China [85]. Lauri et al [31] also found that executing the VMod hydrological model [86] with combined APHRODITE precipitation and NCEP-CFSR temperature inputs accurately replicated hydrological simulations based on surface climate inputs of the 795,000 km 2 Mekong River Basin in southeast Asia.…”
Section: Discussionsupporting
confidence: 93%
“…With regard to GPDs, as has been reported by other authors [56,57], the volumes of precipitation of the satellite precipitation products tended to be smaller than those of the gauged data in most cases, and these differences are greater the drier the watershed is, as in the cases of GAR and RVA. MSWEP and PERSIANN show the highest differences in accumulated precipitation, normally lower, except for the semi-arid watershed (RVA).…”
Section: Discussionsupporting
confidence: 75%
“…First, a behavioral replication was used as a verification method to test whether the model can reproduce both qualitatively and quantitatively the behavior of key parameters [67]. The linear correlation coefficient (CF), Nash-Sutcliff efficiency coefficient (NSE), multiplicative bias (MBias), values of the mean absolute error (MAE), and root mean square error (RMSE) were calculated based on the difference between measured historical data and the simulated data [68,69]:…”
Section: Model Calibration and Validationmentioning
confidence: 99%